Simultaneous effects of silver-decorated graphite nanoplatelets and anisotropic alignments on improving thermal conductivity of stretchable poly(vinyl alcohol) composite films. (November 2020) - Ha, Taeyong; Kim, Dong-Gyun; Ka, Jae-Won; Kim, Yong Seok; Koh, Won-Gun; Lim, Ho Sun; Yoo, Youngjae
Abstract: In this study, graphite nanoplatelets (GNPs), known as a thermally conductive and anisotropic carbon material, was used with polyvinyl alcohol (PVA) as matrix, which is a hydrophilic and biodegradable polymer. In order to expect enhanced thermal conductivity, silver nanoparticle-decorated graphite nanoplatelets (Ag-GNPs) were fabricated by adding silver acetate as a precursor using ' mix-and-heat ' method. Polyvinyl alcohol composite films containing pristine GNPs and Ag-GNPs were prepared using solution casting method. The prepared composite films were uniaxially stretched to induce the filler alignment along the stretching direction as well as the strain-induced crystallization in polymer chains. The effects of the particle size of GNPs, the silver nanoparticle on the surface of GNPs, and the stretching ratios on the thermal conductivity of the composite films were investigated.